(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2024)
The study analyses the family-school relationship at the secondary school stage in the educational centres of the Balearic Islands, Spain. In all cases, there is agreement on the scarce participation of families in the educational community. The studies show that in reality, many families do not participate actively and are not involved in the essential aspects of their children’s education. This study analyses the factors that intervene in the process of family participation, at the same time as proposing a series of didactic proposals to be made with families in the area of Geography and History.